21. PRENATAL DIAGNOSTIC CONGENITAL HEART AND PREGNANCY OUTCOMES AT NGHE AN OBSTETRICS AND PEDIATRICS HOSPITAL 2022 – 2024 (Vietnam Journal of Community Medicine, 2025)
Objective: Review prenatal diagnosis and evaluate pregnancy outcomes of fetuses with congenital heart abnormalities at Nghe An Obstetrics and Pediatrics Hospital in 2022-2024.Method: Retrospective descriptive study of 185 pregnant women with prenatal ultrasound results of congenital heart abnormalities, pregnancy examination and management at the center. The newborn baby was evaluated by echocardiography at the hospital.Results: Among 185 cases of congenital heart abnormalities, the most commonly detected gestational age group was from 21 to 25 weeks, accounting for 31.9%. Prenatal ultrasound assessment showed that simple ventricular septal defect was the most common with 19.6%, followed by tetralogy of Fallot accounting for 16.7%. Atrioventricular canal and hypoplastic left heart syndrome were found in 11.5% and 9.3% of the above cases, respectively. 30.8% of pregnant women who had amniocentesis performed genetic testing and recorded abnormal results of 54.4%, of which 77.4% had abnormal chromosome number, 22.6% had abnormal chromosome structure including DiGeorge, deletion on chromosome 2, duplication on chromosome 1 and 22. Congenital heart defects with increased nuchal translucency accounted for 22.2%, of which 82.1% had genetic abnormalities and up to 36.2% had congenital heart defects combined with other organ abnormalities. Postpartum echocardiography recorded 83.8% of cardiac abnormalities. Fetal edema and stillbirth accounted for a low rate of only 1.6%. There were 5 children who died after birth due to severe congenital heart disease, accounting for 2.7%.Conclusion: Fetal echocardiography has high value in diagnosing cardiac abnormalities. The recommended time for fetal heart examination is between 18 and 22 weeks, although it can be performed earlier.
Keywords: congenital heart defects